Delayed inflammation after biodegradable and osteoconductive osteofixation in orthognathic surgery - Park, Young-Wook (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2024)
This study aims to identify patterns and to describe the clinical course of delayed adverse tissue responses in patients who underwent orthognathic osteotomy with biodegradable osteofixation. Through a retrospective review of cases between 2013 and 2020, we identified three patients who underwent bimaxillary osteotomy and fixation with unsintered-hydroxyapatite/poly-L lactic acid (u-HA/PLLA) devices, after which they developed delayed inflammation. These lesions were treated with drainage and/or removal of the devices. Histological evaluations were conducted using H&E staining, and structural changes in the u-HA/PLLA devices were assessed by scanning electron microscopy (SEM). Inflammatory lesions developed only in the mandible, with onset ranging from 12 to 35 months postoperation. Histological studies identified foreign-body granulomas or secondarily infected lesions. SEM analysis indicated biodegradation and tissue integration. Orthognathic patients treated using u-HA/PLLA devices should be informed about the potential for delayed inflammation and monitored for at least 3 years.